Decision Making for Older Adults With Multiple Chronic Conditions: Executive Summary for the American Geriatrics Society Guiding Principles on the Care of Older Adults With Multimorbidity. Issue 4 (10th March 2019) - Boyd, Cynthia; Smith, Cynthia Daisy; Masoudi, Frederick A.; Blaum, Caroline S.; Dodson, John A.; Green, Ariel R.; Kelley, Amy; Matlock, Daniel; Ouellet, Jennifer; Rich, Michael W.; Schoenborn, Nancy L.; Tinetti, Mary E.
Abstract : Caring for older adults with multiple chronic conditions (MCCs) is challenging. The American Geriatrics Society (AGS) previously developed The AGS Guiding Principles for the Care of Older Adults With Multimorbidity using a systematic review of the literature and consensus. The objective of the current work was to translate these principles into a framework of Actions and accompanying Action Steps for decision making for clinicians who provide both primary and specialty care to older people with MCCs. A work group of geriatricians, cardiologists, and generalists: (1) articulated the core MCC Actions and the Action Steps needed to carry out the Actions; (2) provided decisional tips and communication scripts for implementing the Actions and Action Steps, using commonly encountered situations: (3) performed a scoping review to identify evidence‐based, validated tools for carrying out the MCC Actions and Action Steps; and (4) identified potential barriers to, and mitigating factors for, implementing the MCC Actions. The recommended MCC Actions include: (1) identify and communicate patients' health priorities and health trajectory; (2) stop, start, or continue care based on health priorities, potential benefit vs harm and burden, and health trajectory; and (3) align decisions and care among patients, caregivers, and other clinicians with patients' health priorities and health trajectory. The tips and scripts for carrying out these Actions are included in the full MCC Action Framework available in the supplement (www.GeriatricsCareOnline.org ). J Am Geriatr Soc 67:665–673, 2019.